2019
DOI: 10.3892/etm.2019.7851
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin has a protective effect on atherosclerosis via enhancement of autophagy in ApoE‑/‑ mice

Abstract: The present study examined the involvement of autophagy as a mechanism in the protective effect of quercetin (QUE) on atherosclerosis (AS) in ApoE−/− mice. An AS model was established by feeding ApoE−/− mice a high-fat diet (HFD). Mice were divided into four experimental groups: The model, QUE, 3-methyladenine (3-MA) and QUE + 3-MA groups. Additionally, age-matched wild-type C57BL/6 mice were used as a Control group. Autophagosomes in the aorta were examined using a transmission electron microscope. Aorta path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Both these effects resulted in the retardation of atherosclerotic development. Antioxidant properties of quercetin in atherosclerosis is believed to be implemented through the upregulation of the autophagy in endothelial cells [90,91].…”
Section: Quercetinmentioning
confidence: 99%
“…Both these effects resulted in the retardation of atherosclerotic development. Antioxidant properties of quercetin in atherosclerosis is believed to be implemented through the upregulation of the autophagy in endothelial cells [90,91].…”
Section: Quercetinmentioning
confidence: 99%
“…TNF-α, IL-1β, and IL-18 are the key inflammatory factors between autophagy and inflammation. A previous study revealed that Qu stabilizes AS plaques and inhibits AS development by reducing the production of the proinflammatory cytokines TNF-α, IL-1β, and IL-18, a mechanism which involves the induction of autophagy [83]. Weakened autophagy takes place in all major cell types in AS plaques, resulting in impaired macrophage apoptosis and increased senescence of blood vessel endothelial and smooth muscle cells.…”
Section: Antiapoptosis Activitymentioning
confidence: 99%
“…mTOR, a key molecule in the process of autophagy induction, integrates multiple upstream signaling pathways and interacts with regulator proteins [84]. It also reported that Qu could downregulate the expression levels of mTOR, P53, and cyclin-dependent kinase inhibitor 1A (P21), enhance autophagy, and delay senescence [83]. Autophagy has also been termed as lipophagy, which involves the degradation of intracellular lipid droplets and contributes to cellular lipid metabolism [85].…”
Section: Antiapoptosis Activitymentioning
confidence: 99%
“…Due to its anti‐inflammatory and antioxidant properties, it reduces the oxidative stress via various pathways which include NF‐κB‐dependent mechanism and/or by preventing the activation of pro‐inflammatory or oxidative stress mediators and thereby directly reducing cytokine formation (Gunawardena, Govindaraghavan, & Münch, 2014). It is also found to inhibit fat accumulation in liver of experimental mice on high‐fat diet (Cao, Jia, Shen, et al, 2019; Garelnabi, Mahini, & Wilson, 2014). Quercetin shows therapeutic potential for the prevention and treatment of many diseases such as CVDs, neurodegenerative diseases, and in many forms of cancer (Ay et al., 2016; Wang et al., 2016).…”
Section: Treatment Strategies Using Plant‐based Bioactive Compoundsmentioning
confidence: 99%